Salivary IgA responses to prolonged intensive exercise following caffeine ingestion - Bishop, N. C.; Walker, G. J.; Scanlon, G. A.; Richards, S.; Rogers, E. (Medicine & Science in Sports & Exercise, 2006)
Purpose: Prolonged, intensive exercise is associated with a reduction in concentration and secretion of salivary IgA (s-IgA). Saliva composition and secretion are under autonomic nervous system control, and caffeine ingestion, a widespread practice among athletes for its ergogenic properties, is associated with increased sympathetic nervous system activation. Therefore, this study investigated the influence of caffeine ingestion on s-IgA responses to prolonged, intensive exercise.